2002
DOI: 10.1034/j.1600-0897.2002.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Local Interleukin‐1beta Levels with Specific IgA Response Against Gardnerella vaginalis Cytolysin in Women with Bacterial Vaginosis

Abstract: Induction of the proinflammatory cytokine IL-1beta may be a necessary event to elicit an innate immune response to control anaerobic genital tract infections. High levels of vaginal IL-1beta are associated with mounting of an antigen-specific mucosal immune response in women with bacterial vaginosis. Parallel induction of innate and adaptive immune response may be associated with protection from ascent of micro-organisms to the upper genital tract, and from acquiring viral infection through the vaginal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 49 publications
4
38
0
Order By: Relevance
“…For example, IL-6, IL-8, and MCP-1 can be present in healthy vaginal secretions, [49,50] and the levels are elevated in vaginal secretions during infection with M. hominis or Ureaplasma urealyticum or during intra-amniotic inflammation [51]. IL-1β is consistently higher in genital fluids from women with BV [49,52,53]. However, a recent study by Nakahara et al [54] concluded that IL-1β alone did not induce the phenotypic maturation of MDDC, but maturation required the presence of IFN-γ to induce differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-6, IL-8, and MCP-1 can be present in healthy vaginal secretions, [49,50] and the levels are elevated in vaginal secretions during infection with M. hominis or Ureaplasma urealyticum or during intra-amniotic inflammation [51]. IL-1β is consistently higher in genital fluids from women with BV [49,52,53]. However, a recent study by Nakahara et al [54] concluded that IL-1β alone did not induce the phenotypic maturation of MDDC, but maturation required the presence of IFN-γ to induce differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…IgA antibodies against vaginolysin have been linked to the mucosal immune response during BV, further supporting the role of vaginolysin in BV pathogenesis (Cauci et al, 2002). We analysed the relative cytotoxic activity levels of the BVassociated anaerobes, and found that only G. vaginalis was able to induce rounding and lysis of ME-180 vaginal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased vaginal concentrations of IL-1␤ have been consistently found in women with BV, and HIV. [27][28][29][30] In vaginal fluid, IL-1␤ was positively associated with IL-8 (CXCL8) a potent chemokine. 29 Both of these proinflammatory cytokines were consistently correlated with the number of vaginal neutrophils, in healthy and BV-positive women.…”
mentioning
confidence: 99%